Night Entities in Orion and the Dark (2024) as Representation of Children’s Nyctophobia: A Semiotics Analysis - Nurul Irmah Agustina; Ajeng Rahma Puspita; Mia Fitria Agustina; Ririn Kurnia Trisnawati (Universitas Negeri Semarang, 2026)
Nyctophobia is a fear of the dark that is common among children, especially at night. Stereotypes of night as a quiet, lonely and mysterious time of day reinforce this fear. This study examines how the night entity characters in Orion and the Dark (2024) represent Orion's fear of darkness. While most previous studies have focused on main character or narrative structures, few have explored how supporting characters symbolically shape children’s emotional development. Addressing this gap, the present study interprets the night entities as semiotic representations that influence Orion’s perception of darkness during his childhood. Using a qualitative approach and Barthes' semiotic theory, the analysis shows that denotatively, the night entities are shown in a variety of colors that explicitly describe their behaviors and characters. Connotatively, these colors and behaviors form symbolic meanings related to emotions such as fear, tranquility, and anxiety. These meanings have developed into a myth that night is synonymous with scary things. However, Dark's character who is portrayed as protective becomes a turning point for Orion, showing that night through other entities can also bring serenity and beauty. Hence, through the analysis of signs and meanings based on Barthes’ semiotic framework, this study suggests that positive representations and supportive interactions contribute to reshaping children’s perceptions of darkness, thereby helping to overcome nyctophobia and improve their mental health and well-being.